Thunderbolts : fear itself - Jeff Parker; Kevin Walker (: Marvel, 2012)
When the Serpent's eight mystical hammers fall to Earth, one of them lands on the Raft, the secret headquarters of the Thunderbolts, where Juggernaut picks it up and becomes one of the Serpent's Worthy. Faced with an international crisis and with one of their own now the enemy, the Thunderbolts undergo an identity crisis even as they try to save their team member without getting killed in the process.